The Assessment of Applications for Special Consideration: A Conceptual Framework, Accounting Education - Thompson, P.; Phillips, J.; De Lange, Paul (Elsevier, 2006)
Although the task of reading examination scripts is one of the many pleasures of the practising academic, it is sadly punctuated by the need to assess applications for Special Consideration1. This task would challenge even those who have played Solomon for their country, yet each semester academics are expected to display a flawless exhibition of wisdom, compassion and justice. We have to separate truth from hyperbole without even the benefit of eyeballing the applicant in a locked room with the standard student interview tools of a bright light and rolled bundle of back issues of the British Accounting Review. This Postcard proposes a method of classification of the types of students who make application for Special Consideration, and proposes a complementary classification of assessment approaches adopted by academics. By cross-referencing the two classifications, we summarize the potential outcomes of the Special Consideration assessment process. It should be noted that the substance of these cases were presented by students in their efforts to gain Special Consideration.